2019
DOI: 10.1002/dev.21834
|View full text |Cite
|
Sign up to set email alerts
|

Female pups receive more maltreatment from stressed dams

Abstract: The effects of exposure to developmental stress often diverge for males and females. Using the scarcity‐adversity model of low nesting resources outside the home cage, our lab has discovered sex differences in both behavioral and epigenetic consequences of repeated exposure to caregiver maltreatment. For the measures we have performed to date, we have found more consequences for females. The reasons underlying this sex disparity are unknown. In the current experiment, we aimed to discern the quality of materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…First, there are sex differences in basal levels of epigenetic modifications (Kurian et al, 2010; Nugent et al, 2015; Tsai et al, 2009) and enzymes (Blaze and Roth, 2013; Kigar et al, 2016; Kolodkin and Auger, 2011; Kurian et al, 2007; Xu et al, 2008a, 2008b), which may affect the female epigenetic response to both maltreatment and epigenome‐modifying drugs. Second, recent data from our lab show that females experience a higher proportion of adverse care in our maltreatment paradigm than do male pups (Keller et al, 2019). Given that male pups are subject to increased nurturing (licking) behavior in the home cage (Moore and Morelli, 1979; Richmond and Sachs, 1984), females subject to our brief exposures of maltreatment are overall experiencing more adverse and less nurturing behaviors than male pups subject to the same exposures.…”
Section: Discussionmentioning
confidence: 86%
“…First, there are sex differences in basal levels of epigenetic modifications (Kurian et al, 2010; Nugent et al, 2015; Tsai et al, 2009) and enzymes (Blaze and Roth, 2013; Kigar et al, 2016; Kolodkin and Auger, 2011; Kurian et al, 2007; Xu et al, 2008a, 2008b), which may affect the female epigenetic response to both maltreatment and epigenome‐modifying drugs. Second, recent data from our lab show that females experience a higher proportion of adverse care in our maltreatment paradigm than do male pups (Keller et al, 2019). Given that male pups are subject to increased nurturing (licking) behavior in the home cage (Moore and Morelli, 1979; Richmond and Sachs, 1984), females subject to our brief exposures of maltreatment are overall experiencing more adverse and less nurturing behaviors than male pups subject to the same exposures.…”
Section: Discussionmentioning
confidence: 86%
“…Further complicating findings related to rodent sex differences induced by ELS is the fact that rodent dams exhibit greater maternal care for male versus female pups (Hao, Huang, Nielsen, & Kosten, 2011;Keller, Nowak, & Roth, 2019;Moore & Morelli, 1979;Richmond & Sachs, 1984). And as mentioned previously, ELS rodent models produce varied effects depending upon species and strain, so additional future studies specific to C57BL/6J mice will help ascertain whether ELS exerts BNST-mediated effects that are dependent upon sex.…”
Section: Bnst-mediated Sex Effectsmentioning
confidence: 99%
“…In addition, it also agrees with previous studies showing that female animals are more vulnerable to the effects of early life stress in a wide range of behavioural and neurobiological outcomes 42 , 43 . According to Keller et al 44 , the increased vulnerability in females may be related to impaired maternal care. These authors showed that in a maltreatment condition, female offspring received higher adverse care from the dams than male offspring.…”
Section: Discussionmentioning
confidence: 99%